2022
DOI: 10.1039/d1cy01584b
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium ionic liquid cation promotes electrochemical CO2 reduction to ethylene over formate while inhibiting the hydrogen evolution on a copper electrode

Abstract: Reduction in the cost of renewable electricity has enhanced the viability of electrochemical CO2 reduction reaction (CO2RR) to chemicals. Ethylene is an economically desired product, and Cu is the only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…The electrochemical CO 2 reduction reaction (CO 2 RR) can utilize CO 2 by valorizing it into fuels and basic chemicals. 1,2 Recent advances in CO 2 electroreduction have been motivating academia and industry to look into the economic viability of this technology. Therefore, many TEA analyses were carried out to find the threshold for profitability.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical CO 2 reduction reaction (CO 2 RR) can utilize CO 2 by valorizing it into fuels and basic chemicals. 1,2 Recent advances in CO 2 electroreduction have been motivating academia and industry to look into the economic viability of this technology. Therefore, many TEA analyses were carried out to find the threshold for profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazolium modifiers have been investigated to improve the selectivity and overpotential of CO, formate, and ethylene productions on various electrodes. Although the mechanism of the promotion effect is still under debate, previous studies have suggested that the imidazolium modifiers play important roles in increasing the CO 2 adsorption and stabilizing a CO 2 anion radical intermediate by specific interactions . For example, Dyson and Grätzel groups have found that changing the substituents of C4- and C5- other than C2-positions on the imidazolium ring have pronouncing effects on the catalytic activity of Ag .…”
Section: Introductionmentioning
confidence: 99%
“…Ummireddi et al used a mixed aqueous solution of KHCO 3 (0.1 M) and IL (1 mM) as electrolyte. [90] Four ILs were used, which have identical anion (tetrafluoroborates, BF 4 À ) and the cations were 1-butyl-2-methylpyrazolium (BMPyra + ), tetraethylammonium (TEA + ), 1-butyl-3-methylimidazolium (BMIm + ) and 1-butyl-1-methylpyrrolidinium (BMPyrro + ), respectively. It was found that TEA + , which has a moderate Bader charge of N atom (À 0.83), is the most efficient in producing C 2 H 4 .…”
Section: Electrolytementioning
confidence: 99%